Generation and Evolution Conditions of Polygonal Wear of High-Speed Wheel - Yahong Dong; Shuqian Cao (Shock and Vibration)
Wheel polygonal wear has long been a problem that confused the safety of railway operation which has important theoretical value and research significance. In this paper, the conditions of polygonal wear of high-speed wheel are analyzed based on the wear model and verified by the field measured data. Considering the wheel track interaction caused by rotation, a finite element model of wheelset rotor dynamics is established. The effects of rotor speed, mass eccentricity, wheelset, and track flexibility on the vibration characteristics of wheelset rotor system and wheel polygonal wear characteristics are analyzed by beam element and solid element, respectively. The results show that the wheel longitudinal vibration is the main reason of wheel polygonal wear, and the wheel polygonal wear follows the law of “constant frequency and divisible.” Its “constant frequency” comes from the wheel track contact vibration, which stimulates the third-order vertical bending vibration of wheelset and the eighth-order coupled bending vibration of track, and the order is equal to the ratio of “constant frequency” to the wheelset rotation frequency.